Analysis of Fundamental Factors Affecting Stock Prices - Harjadi, Dikdik; Komarudin*, Munir Nur; Fitriani, Lili Karmela; Indriarto, Enricho Dwi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This study aims to determine the effect of profitability, solvency, liquidity, and market value on stock prices. The population and samples used were 22 mining companies. The sampling technique used was purposive sampling with descriptive and verification analysis methods, and using Eviews 9. The data analysis technique used was panel data regression analysis. Based on the results of the F test, shows that profitability, solvency, liquidity, and market value together have a significant effect on stock prices. Also, the results of the t-test show that profitability has no effect on stock prices, while solvency has a significant effect on stock prices, liquidity has a significant effect on stock prices and finally, market value also has a significant effect on stock prices. The implication of this research is that the company is expected to keep the company in a solvable state by being aware of the amount of debt it has because it will bring the risk of non-payment of debt. Keywords: Profitability; Solvency; Liquidity; Market Value; Stock Price